Wood et al 2016 Bewick Swan breeding success paper data - Wood, Kevin A.; Newth, Julia L.; Hilton, Geoff M.; Nolet, Bart A.; Rees, Eileen C. (Dryad Digital Repository, 2016)
A Microsoft Excel spreadsheet containing the raw and standardized values for all variables used in the analysis of Bewick's Swan breeding success. The data cover the period 1988-2013. A legend describing the identity of each variable is also included. Further information on the data analysis is available in the published paper.